2021
DOI: 10.1016/j.radcr.2021.02.053
|View full text |Cite|
|
Sign up to set email alerts
|

Embolization of uterine arteriovenous malformation causing postpartum hemorrhage using n-butyl cyanoacrylate: A case report

Abstract: Uterine artery arteriovenous malformations (AVMs) are rare anomalies that may result in uterine hemorrhage. A 40-year-old G8P5126 woman presented with severe vaginal bleeding and an estimated 2000 mL of blood loss at home. Three weeks prior, she had a vaginal delivery of a term infant resulting in post-partum hemorrhage, with 2700 mL of blood loss. The patient had a history of ectopic pregnancy, placenta previa, and dilatation and curettage. Interventional radiology was consulted, and the patient underwent ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The effect of leonurusine on hemorheology may be related to the dilation of blood vessels and the reduction of fibrinogen content. Motherwort injection is a colorless liquid of 20 mg hydrazine per 1 mL obtained by water extraction and alcohol precipitation of motherwort, advantageous formulation developed for motherwort, and it is widely used clinically to prevent and treat postpartum hemorrhage and promote postpartum uterine involution [ 15 ]. Qin Xianfen reported that the half-life of oxytocin is 1–6 minutes, motherwort injection is about 6 hours, and the combination of the two has a synergistic effect; when the effect of oxytocin diminishes, motherwort injection can still promote uterine contractions and enhance the hemostatic effect; it can effectively avoid the slow onset of motherwort [ 16 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The effect of leonurusine on hemorheology may be related to the dilation of blood vessels and the reduction of fibrinogen content. Motherwort injection is a colorless liquid of 20 mg hydrazine per 1 mL obtained by water extraction and alcohol precipitation of motherwort, advantageous formulation developed for motherwort, and it is widely used clinically to prevent and treat postpartum hemorrhage and promote postpartum uterine involution [ 15 ]. Qin Xianfen reported that the half-life of oxytocin is 1–6 minutes, motherwort injection is about 6 hours, and the combination of the two has a synergistic effect; when the effect of oxytocin diminishes, motherwort injection can still promote uterine contractions and enhance the hemostatic effect; it can effectively avoid the slow onset of motherwort [ 16 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The follow-up abdominal CTA at 8 weeks after the procedure showed no residual AVM, and the patient was healthy with no longer abnormal bleeding at 3-year follow-up. or therapeutic intervention, as focused on in several studies [11][12][13][14][15][16][17]. This is due to the fact that the effectiveness of diagnosis leading to definitive treatment is primarily based on the first significant clues obtained from routine ultrasound in actual practice.…”
Section: Case 1 (Figure 1)mentioning
confidence: 99%
“…Several non-invasive diagnostic modalities have been used to diagnose uterine AVM, such as computed tomography angiography (CTA), magnetic resonance imaging (MRI), color flow Doppler ultrasound, three-dimensional (3D) ultrasound, power Doppler angiography, and amplitude-mode color Doppler ultrasound. Nevertheless, this study exclusively emphasizes its sonographic features as essential primary tools for the diagnosis of uterine AVM, instead of back-up tools, like computed tomography angiography (CTA), or therapeutic intervention, as focused on in several studies [11][12][13][14][15][16][17]. This is due to the fact that the effectiveness of diagnosis leading to definitive treatment is primarily based on the first significant clues obtained from routine ultrasound in actual practice.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the imaging findings, evaluation of potential extra-uterine feeding arteries may also be pertinent. The choice of embolic is operator dependent, but gelfoam, particles, coils and liquid embolic agents have all been described (Wang et al, 2012 ; Giurazza et al, 2017 ; Stiepel et al, 2021 ; Yoon et al, 2016 ) (Fig. 8 ).…”
Section: Approach To Vascular Injuries and Anomaliesmentioning
confidence: 99%
“…Our preference is to avoid particle embolics including gelfoam to reduce the theoretical risk of non-target embolization through the shunt. Embolization of uterine AVFs can yield durable long-term results with no evidence of recurrence or residual arteriovenous fistula (Wang et al, 2012 ; Giurazza et al, 2017 ; Stiepel et al, 2021 ; Yoon et al, 2016 ).
Fig.
…”
Section: Approach To Vascular Injuries and Anomaliesmentioning
confidence: 99%